2001
DOI: 10.1017/s0022112001005808
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale modes of turbulent channel flow: transport and structure

Abstract: Turbulent flow in a rectangular channel is investigated to determine the scale and pattern of the eddies that contribute most to the total turbulent kinetic energy and the Reynolds shear stress. Instantaneous, two-dimensional particle image velocimeter measurements in the streamwise-wall-normal plane at Reynolds numbers Reh = 5378 and 29 935 are used to form two-point spatial correlation functions, from which the proper orthogonal modes are determined. Large-scale motions – having length scales of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
127
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 23 publications
20
127
0
1
Order By: Relevance
“…This type of analysis was introduced to the fluids community by Lumley [168] and has since been used extensively in analyzing turbulent and transitional flows (e.g., Refs. [23,38,133,[169][170][171]). The methodology of POD is outlined in detail by Berkooz et al [169] but, the method used in this investigation is based on the snapshot method as discussed by Sirovich [172].…”
Section: Streamwise Flow Developmentmentioning
confidence: 99%
“…This type of analysis was introduced to the fluids community by Lumley [168] and has since been used extensively in analyzing turbulent and transitional flows (e.g., Refs. [23,38,133,[169][170][171]). The methodology of POD is outlined in detail by Berkooz et al [169] but, the method used in this investigation is based on the snapshot method as discussed by Sirovich [172].…”
Section: Streamwise Flow Developmentmentioning
confidence: 99%
“…These observations provide further evidence that vortex organization is a dominant feature of the outer layer. With regard to transport, Liu et al 9 found that large-scale motions having length scales on the order of the channel half-height can be reconstructed with only a few low-order proper orthogonal decomposition ͑POD͒ modes. These low-order modes contained half of the turbulent kinetic energy and over two-thirds of the Reynolds shear stress in the outer region.…”
Section: Introductionmentioning
confidence: 99%
“…As a given portion of a turbulent flow is composed of structures of varying age and levels of activity, ensemble-averaged approaches may present a more complicated or confused picture of the flow than actually exists. Liu, Adrian & Hanratty (2001), Adrian, Meinhart & Tomkins (2000) and Zhou et al (1999) have provided insight on the generation of coherent hairpin vortex packets containing a multiplicity of spatially organized hairpin-like vortices in channel and boundary-layer flows. The earlier observations by Bandyopadhyay (1980) and Head & Banyopadhyay (1981) on these packets with a characteristic upstream interface, sloping at about 12 • to 20 • , were confirmed using numerical simulations and PIV experiments.…”
Section: Introductionmentioning
confidence: 99%